Limitations of administrative data to identify measles cases in Ontario, Canada: a cautionary tale - Johnson, Caitlin (Can J Public Health, 2018)
OBJECTIVE: To explore the utility of laboratory data and determine the validity of healthcare administrative data for describing the frequency of measles in Ontario. METHODS: We linked Ontario healthcare utilization administrative data to Public Health Ontario (PHO) laboratory data from 01 January 2006 to 30 November 2012. RESULTS: The sensitivity of the administrative data was 54% and the positive predictive value was 1% when compared with 50 cases identified in laboratory data as a gold standard. CONCLUSIONS: As measles is no longer endemic in Ontario, the high number of measles-coded healthcare visits found in Ontario health administration data exceeds the true number of cases. Great caution should be taken in using administrative data to calculate the incidence of measles in areas where it has been eliminated.